2012
DOI: 10.1080/00387010.2011.599827
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Absorption Studies on Formaldehyde Using Synchrotron Radiation at Indus I

Abstract: Photo-absorption spectra of formaldehyde (HCHO) is recorded in the range of 6-11.5 eV at various pressures (<0.001-2 mbar) at an average resolution of 1.2 Å using Photophysics beam line at the 450 MeV Indus-1 synchrotron radiation facilities at RRCAT Indore, India. The spectrum is found to consist exclusively of n ! Rydberg transitions converging to the ground state of HCHO þ . The highest identified Rydberg states, observed up to the first ionization limit of HCHO, correspond to 7s, 11p, 9d, and 12f orbitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Considering the ionisation energy, we emphasise the remarkable agreement between the B3LYP calculated value and the experimental value by Paiva et al [7], which differ by 0.5 %, and the FCI calculated value lies more than 0.5 eV above the result of Terlouw et al The 5.5 eV energy value for the S 0 →S 1 transition, calculated in the CIS framework, is in good agreement, given the well documented overestimation of CIS excitation energies [32][33][34], with the experimental values of 4.55 ± 0.01 eV and 4.45 ± 0.01 eV, obtained by Uno et al [5] and Paiva et al [10], respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Considering the ionisation energy, we emphasise the remarkable agreement between the B3LYP calculated value and the experimental value by Paiva et al [7], which differ by 0.5 %, and the FCI calculated value lies more than 0.5 eV above the result of Terlouw et al The 5.5 eV energy value for the S 0 →S 1 transition, calculated in the CIS framework, is in good agreement, given the well documented overestimation of CIS excitation energies [32][33][34], with the experimental values of 4.55 ± 0.01 eV and 4.45 ± 0.01 eV, obtained by Uno et al [5] and Paiva et al [10], respectively.…”
Section: Discussionsupporting
confidence: 82%
“…The experimental excitation energy of Uno et al [5] and experimental ionisation energies of Terlouw et al [6] and Paiva et al [7] are also shown for comparison. It is well documented in the literature [32][33][34] that the CIS method overestimates excitation energies substantially (typically by 1-2 eV), hence we can compare the excitation energy of 5.5 eV, obtained in Table 3. Experimental and theoretical adiabatic ionisation energies ( E) and first excited-state transition energy of diphenyl ether (Ph 2 O).…”
Section: Torsional Barriersmentioning
confidence: 98%
“…8) is composed of vibronic Rydberg transitions where the Rydberg transitions are intense and the vibrational progression are weak. 81,82 The Rydberg transitions resulting from the ground state ( 1 A 1 ) have been previously observed using a VGA 101 VUV spectrometer. 81,[83][84][85] However, the vibrational transitions were not distinguishable.…”
Section: Formaldehydementioning
confidence: 99%